Sustainable Desert Tourism as a Way to Promote Internal Tourism in Algeria Study of The Experiences of Some Arab Countries - Medjdoub, Khayra; Tawiti, Mostapha (Finance and Business Economies Review, 2019)
This study address the issue of sustainable tourism development desert by highlighting the elements of attraction of desert tourism in the Arab world in general and the Arab Maghreb in particular, to submit a proposal on how to optimize the use and successful recruitment of natural resources while creating the right climate to attract investment in the context of achieving ecological balance integrated between the vocabulary of the desert environment and the needs of tourism development to give the perception of an insurance mechanism for the ecosystem, and display as well as the experiences of some countries of the Maghreb (Algeria, Tunisia and Mauritania) in the field of sustainable desert tourism.